POTENSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) TERHADAP PENGHAMBATAN Candida albicans DAN Propionibacterium acnes - Saat Egra; Irawan Wijaya Kusuma; Enos Tangke Arung (ULIN: Jurnal Hutan Tropis, 2018)
Oyster mushroom (Pleurotus ostreatus) is not a new food for the community. Long time ago oyster mushrooms is food but not so well known. Now oyster mushrooms have been accepted by the community as a healthy food. This is the background of this research to produce mushrooms not only as nutritious food but also natural medicine. The purpose of this study was to examine the antimicrobial potential of oyster mushrooms by determination of clear zone against Candida albicans and Propionibacterium acnes bacterias. This research was conducted at Forest Products Chemistry Laboratory, Faculty of Forestry, Mulawarman University. The resources of oyster mushroom we used in this study comes from the cultivation of the entrepreanure forestry student group in Mulawarman University. This study used successful extraction with hexane solvent, ethyl acetate, ethanol, water, and crude ethanol. The results obtained that the highest antimicrobial inhibition against Candida albicans bacteria with 47.60% with a concentration of 100 ppm but, on the antimicrobial against Propionibacterium acnes bacteria did not show any significant inhibition.